Rodzina szlachecka jako miejsce wychowania i szkolenia wojskowego w okresie staropolskim - Ciupińska, Barbara; Ryś, Jan (Karkonoska Państwowa Szkoła Wyższa, 2011)
In an Old Polish period a family house had a very significant role in education and military preparation. Due to lack of military schools it was the only source of patriotic and military education. The atmosphere of constant thread evoked by ceasless wars caused that the youth was prepared to defence and military service since the earliest years. Patriotic and defensive education was supervised by father and appointed tutors. It was shaped also by the traditios of the noble house, interior decoration and fumishings, as well as specially prepared and selected military playthings and games. A father was a first person who introduced a son into the depths of military art.
Keywords: military education; family upbringing; noble family